2016
DOI: 10.4315/0362-028x.jfp-16-106
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Dispersal of Indicator Bacteria on Cucumbers Grown Horizontally or Vertically on Various Mulch Types

Abstract: No data exist on the impact of cultivation practices on food safety risks associated with cucumber. Cucumbers are typically grown horizontally over a mulch cover, with fruit touching the ground, but this vining plant grows well in vertical systems. To assess whether production system affects bacterial dispersal onto plants, field trials were conducted over 2 years. Cucumber cultivar 'Marketmore 76' was grown horizontally on plastic, straw, or bare ground or vertically on trellises installed on bare ground in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Often the limited data available conflicted in terms of the practice's foodsafety impacts. For example, one of the two studies that evaluated mulch applications found that E. coli prevalence was not associated with mulch application, while the second study found that E. coli sometimes survived longer in soils with mulch applied (Micallef et al, 2016;Xu et al, 2016). Though there were more studies that examined the food-safety impact of tillage (N = 5 studies), results were still inconclusive, and most studies reported no effects on foodborne pathogens (Endale et al, 2010;Bezanson et al, 2012;Jenkins et al, 2014;Reed-Jones et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Often the limited data available conflicted in terms of the practice's foodsafety impacts. For example, one of the two studies that evaluated mulch applications found that E. coli prevalence was not associated with mulch application, while the second study found that E. coli sometimes survived longer in soils with mulch applied (Micallef et al, 2016;Xu et al, 2016). Though there were more studies that examined the food-safety impact of tillage (N = 5 studies), results were still inconclusive, and most studies reported no effects on foodborne pathogens (Endale et al, 2010;Bezanson et al, 2012;Jenkins et al, 2014;Reed-Jones et al, 2016).…”
Section: Figurementioning
confidence: 99%